2016
DOI: 10.1177/1533317516680899
|View full text |Cite
|
Sign up to set email alerts
|

Can We Help Care Providers Communicate More Effectively With Persons Having Dementia Living in Long-Term Care Homes?

Abstract: Background:Effective communication between residents with dementia and care providers in long-term care homes (LTCHs) is essential to resident-centered care.Purpose:To determine the effects of a communication intervention on residents’ quality of life (QOL) and care, as well as care providers’ perceived knowledge, mood, and burden.Method:The intervention included (1) individualized communication plans, (2) a dementia care workshop, and (3) a care provider support system. Pre- and postintervention scores were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(81 citation statements)
references
References 35 publications
2
78
0
1
Order By: Relevance
“…They further stated that the training would impact on care delivery as they were now more aware of the unique needs of each individual resident. The final study in the intervention category focused on communication workshops; however, no significant difference was found in levels of confidence or competence following training …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They further stated that the training would impact on care delivery as they were now more aware of the unique needs of each individual resident. The final study in the intervention category focused on communication workshops; however, no significant difference was found in levels of confidence or competence following training …”
Section: Resultsmentioning
confidence: 99%
“…The final study in the intervention category focused on communication workshops; however, no significant difference was found in levels of confidence or competence following training. 19 Non-intervention studiessense of confidence The first of the two non-intervention studies focusing on confidence was a needs assessment addressing knowledge deficits in caring for people with BPSD. 24 Data were not statistically analyzed, but it was found that only one-fifth of staff felt confident in managing BPSD with non-pharmacological approaches.…”
Section: Study Characteristicsmentioning
confidence: 99%
“… [ 55 ] McGilton et al Canada Hearing and vision screening tools for long-term care residents with dementia: protocol for a scoping review 2016 Journal article—protocol for pilot study The pilot study looking at effective screening tool for residents with dementia and communication impairment: hearing and vision. [ 44 ] McGilton et al Canada Can we help care providers communicate more effectively with persons having dementia living in long-term care homes? 2017 Journal article—mixed methods study Determine the effects of a communication intervention on residents’ quality of life (QOL) and care, as well as care providers’ perceived knowledge, mood, and burden.…”
Section: Resultsmentioning
confidence: 99%
“…Such games may also be a good way to assess cognitive status of PwD in a nonthreatening way [ 119 - 123 ]. Future work should also consider cultural and language aspects that may affect performance and engagement (for a discussion, see [ 124 ]), as well as aspects of the testers themselves [ 125 ].…”
Section: Discussionmentioning
confidence: 99%